Relasi Pemikiran Nabia Abbott dan Ignaz Goldziher dalam Studi á¸¤adÄ«th - Muawanah, Arofatul (Islamika Inside: Jurnal Keislaman dan Humaniora, 2017)
Among the Orientalists, who have different ideas, are Ignaz Goldziher and Nabia Abbott. In his study, Goldziher always show a sharp criticism of the scientific construction of á¸¥adÄ«th and his views on á¸¥adÄ«th have been always dissimilar with scholars of á¸¥adÄ«th. He also alleges that the existence of á¸¥adÄ«th is no longer original. Abbottâ€™s thought of á¸¥adÄ«th, in contrast, tends to be moderate. Broadly speaking, Abbottâ€™s views seem to reinforce the thought of â€˜ulamÄâ€™ al-á¸¥adÄ«th. Abbott even acknowledges that the compilation of á¸¥adÄ«th has existed since the Prophet Muhammadâ€™s lifetime. In this context, it is interesting to note that Goldziher and Abbott are equally orientalists who employ the Western paradigm in examining á¸¥adÄ«th. The question is whether there is a relationship of thought between the two. Using descriptive and analytical methods this article specifically traces and explores the relationship of Abbott and Goldziherâ€™s thoughts. The study aims to determine the extent to which the relation of thought between the two Orientalists and the factors affect the similarity of thought between them.